'The phone means everything.' Mobile phones, livelihoods and social capital among Syrian refugees in informal tented settlements in Lebanon. (1st September 2020) - Göransson, Markus Balázs; Hultin, Lotta; Mähring, Magnus
ABSTRACT: This study explores the role of mobile phones in livelihood creation among Syrian refugees in informal tented settlements in Akkar Governorate and the Bekaa Valley in Lebanon. Drawing on forty-five interviews with Syrian refugees and ten interviews with aid workers, the study highlights the importance of mobile phones in reviving, maintaining and leveraging social capital for the purpose of securing livelihoods in a context of precarity and restricted movement. We find that mobile phones offer important means for reviving social networks in exile, managing supportive relationships that have been established in Lebanon and liaising with employers. As such, they constitute important tools for coping with a context shaped by legal exclusion, restricted movement, police harassment, decentralised aid provision and a geographical dispersal of support networks, even as they remain a costly investment with uncertain returns.